1985
DOI: 10.1038/bjc.1985.79
|View full text |Cite
|
Sign up to set email alerts
|

Cell selection from a murine tumour using the fluorescent probe Hoechst 33342

Abstract: Images Figure 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(44 citation statements)
references
References 8 publications
(11 reference statements)
1
43
0
Order By: Relevance
“…Chaplin et al (1985Chaplin et al ( , 1986Chaplin et al ( , 1987 Loeffler et al, 1987). The sorted populations that result should be derived from different locations within the tumour relative to the blood supply at the time of staining.…”
mentioning
confidence: 99%
“…Chaplin et al (1985Chaplin et al ( , 1986Chaplin et al ( , 1987 Loeffler et al, 1987). The sorted populations that result should be derived from different locations within the tumour relative to the blood supply at the time of staining.…”
mentioning
confidence: 99%
“…Both panels of Figure 1 show cellular radiosensitivity as a function of Hoechst staining intensity; in spheroids, the symmetry of the model allows an easy calculation of the depth from which the cells were recovered (Durand, 1983), while in the tumour system, the data are simply presented as fraction number, where fraction I represented the 10% of the cells which were most intensely stained (thus nearest the functional blood supply, e.g. Chaplin et al, 1985Chaplin et al, ,1986a (Figure 2) indicated that the less well oxygenated cells were more sensitive to this nitrosourea, in agreement with previous results obtained with nitrosoureas in other spheroid systems (Deen et al, 1980;Kwok & Twentyman, 1985). Quite reproducible responses were found in the multiple experiments shown (note that in the case of spheroids, different starting sizes led to slightly different estimates of cell depth among experiments).…”
Section: Resultsmentioning
confidence: 99%
“…Cells were recognized by the forward scatter signal; the resulting signals from the Hoechst stain and the 900 scatter signals were processed through matched logarithmic amplifiers, and the ratio of these signals used to generate a 'stain concentration' profile which was integrated to define 10 windows of equal cell numbers each (Durand, 1983). A stained but untreated tumour or spheroid cell population was used to define the plating efficiency of each sorted fraction; as in previous studies (Durand, 1982(Durand, , 1983Chaplin et al, 1985Chaplin et al, , 1986a, no systematic variation was observed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This dye penetrates tumour tissue producing a gradient of fluorescence (visible in the u.v. range) that identifies the position of cells in situ relative to any functional vasculature (Chaplin et al, 1985). Mice were given 0.1 ml intravenous injections of Hoechst 33342 20 minutes prior to tumour excision.…”
Section: Immune Cell Determinationmentioning
confidence: 99%